Organizational behavior and management in Philippine organizations - Zarate, Cynthia A (Manila, 2006)
This book provides readings on certain topics that the author feels would be useful in facing e challenges of modernization and globalization. Students should prepared in facing these challenges and be equipped with the hniques and strategies in establishing relationships with co-ployees and attaining organizational objectives.
Keywords: Human Behavior in organizations- Philippines; Organizational Behavior-Philippines